Nucleolar KKE/D repeat proteins Nop56P and Nop58P interact with Nop1p and are required for ribosome biogenesis - Gautier, Thierry; Bergès, Thierry; Tollervey, David; Hurt, Ed (Molecular and cellular biology, 1997)
Different point mutations in the nucleolar protein fibrillarin (Nop1p in Saccharomyces cerevisiae) can inhibit different steps in ribosome synthesis. A screen for mutations that are synthetically lethal (sl) with the nop1-5 allele, which inhibits pre-rRNA processing, identified NOP56. An independent sl mutation screen with nop1-3, which inhibits pre-rRNA methylation, identified a mutation in NOP58. Strikingly, Nop56p and Nop58p are highly homologous (45% identity). Both proteins were found to be essential and localized to the nucleolus. A temperature-sensitive lethal mutant allele, nop56-2, inhibited many steps in pre-rRNA processing, particularly on the pathway of 25S/5.8S rRNA synthesis, and led to defects in 60S subunit assembly. Epitope-tagged constructs show that both Nop56p and Nop58p are associated with Noplp in complexes, Nop56p and Nop1p exhibiting a stoichiometric association. These physical interactions presumably underlie the observed sl phenotypes. Well-conserved homologs are present in a range of organisms, including humans (52% identity between human hNop56p and yeast Nop56p), suggesting that these complexes have been conserved in evolution.
Elektronische Reproduktion der Druck-Ausgabe 29. März 2023
Gesehen am 01.12.2025